FORMULATION AND CHARACTERISTICS OF SOLID PERFUME FROM LEMONGRASS OIL WITH VARIATION BEESWAX AND ESSENTIAL OIL - Yunus, Muhammad; Amalia, Zuhra; Ridwan, R; Aida, Atiqah; Ilmi, Awanis (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT The potential availability of abundant essential oil plants in Indonesia is very beneficial for the community. One of the essential oil plants that can be utilized for its potential is citronella. Citronella oil can be formulated into solid perfume as an innovation to replace liquid perfume. This study aims to formulate and characterize solid perfume from various variations of beeswax concentration (30%, 40%, 50%), citronella (1%, 3%, 5%) and several note parfume. The solid perfume was characterized by observing the density value, boiling point value, organoleptic test and functional group test. The results showed that the highest density value of 0.9786 gr/ml and the melting point value of 69°C were in the 50% beeswax formulation and 1% citronella oil concentration. The lowest solid perfume density value of 0.9350 gr/ml and melting point value of 61°C were in the 30% beeswax formulation with 5% citronella oil concentration. FT-IR testing results, the solid perfume produced has the same functional groups in the mixture of raw materials made. This indicates that no new compounds are formed. The results of organoleptic testing show that solid perfume with 40% beeswax composition and 1% concentration is the most preferred. Keywords: Solid Perfume, Citronella Oil, Beeswax, Density